2021
DOI: 10.1167/iovs.62.2.31
|View full text |Cite
|
Sign up to set email alerts
|

EMC3 Is Essential for Retinal Organization and Neurogenesis During Mouse Retinal Development

Abstract: Purpose We used a mouse model to explore the role of the endoplasmic reticulum membrane protein complex subunit 3 (EMC3) in mammalian retinal development. Methods The transcription pattern of Emc3 in C57BL/6 mice was analyzed by in situ hybridization. To explore the effects of EMC3 absence on retinal development, the Cre-loxP system was used to generate retina-specific Emc3 in knockout mice (Emc3 flox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…3 months after treatment, the rabbits’ eyes were enucleated after euthanasia and fixed in 10% formalin. Subsequently, 4 μm of paraffin-embedded slices were prepared and then stained with hematoxylin and eosin (HE, Aldrich-Sigma, USA) based on routine procedures . The slides were then examined using an inverted microscope (Olympus, Japan) and reviewed independently by two blinded observers stochastically.…”
Section: Methodsmentioning
confidence: 99%
“…3 months after treatment, the rabbits’ eyes were enucleated after euthanasia and fixed in 10% formalin. Subsequently, 4 μm of paraffin-embedded slices were prepared and then stained with hematoxylin and eosin (HE, Aldrich-Sigma, USA) based on routine procedures . The slides were then examined using an inverted microscope (Olympus, Japan) and reviewed independently by two blinded observers stochastically.…”
Section: Methodsmentioning
confidence: 99%
“…EMC3 is homologous to known membrane protein insertases Oxa1 family proteins ( Volkmar and Christianson, 2020 ; Wideman, 2015 ), and depletion of EMC3 results in ER stress and activates the unfolded protein response ( Huang et al., 2021 ; Tang et al., 2017 ). Moreover, EMC3 was reported to coordinate the assembly of lipids and proteins required for surfactant synthesis ( Tang et al., 2017 ), maintain differentiation and function of intestinal exocrine secretory lineages ( Huang et al., 2021 ), and play a critical role in mammalian retinal development ( Cao et al., 2021 ; Zhu et al., 2020 ). In parallel, in addition to its role in regulating the biogenesis of acetylcholine receptors in C. elegans ( Richard et al., 2013 ), EMC6 was reported to regulate the autophagosome formation, and knocking down EMC6 impaired autophagy ( Li et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…EMC3 is homologous to known membrane protein insertases Oxa1 family proteins (Volkmar and Christianson, 2020; Wideman, 2015), and depletion of EMC3 results in ER stress and activates the unfolded protein response (Huang et al, 2021; Tang et al, 2017). Moreover, EMC3 was reported to coordinate the assembly of lipids and proteins required for surfactant synthesis (Tang et al , 2017), maintain differentiation and function of intestinal exocrine secretory lineages (Huang et al , 2021), and play a critical role in mammalian retinal development (Cao et al, 2021; Zhu et al, 2020). In parallel, in addition to its role in regulating the biogenesis of acetylcholine receptors in C. elegans (Richard et al , 2013), EMC6 was reported to regulate the autophagosome formation and knocking down EMC6 impaired autophagy (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%